Corrosion Resistance of DLC Film-Coated SUS316L Steel Prepared by Ion Beam Enhanced Deposition - Bei B. Han; Dong Y. Ju; Mao R. Chai; Hui J. Zhao; Susumu Sato (Advances in Materials Science and Engineering)
In order to improve the conductivity and anticorrosive resistance of bipolar plates in fuel cells, the characterizations and corrosion behaviors of the DLC-coated SUS316L steel deposited with different gas ratios CH4/H2 and deposition times were investigated and evaluated. The chemical bonding structure and composition of the DLC coatings were confirmed by Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The micromorphology and surface roughness of the DLC were observed by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The element compositions of cross section were determined by electron probe microanalysis (EPMA). The interfacial contact resistance (ICR) was measured. Furthermore, the DLC-coated SUS316L steel was corroded by potentiostatic polarizations in a 0.5 M H2SO4 solution at 0.8 V, 90°C for 168 h, and the corrosion behaviors were investigated in the solution using electrochemical techniques. In addition, the metal ions in sulfuric acid corrosion solution were detected by inductively coupled plasma-atomic emission spectroscopy. The results indicate that the DLC coatings deposited at a lower gas ratio CH4/H2 of 1 : 1 could result in a decreasing ID/IG ratio of 1.03, low Ra roughness of 3.77 nm, low ICR of 12.9 mΩ cm2, and low metal ion concentration of 16.60 ppm in the corrosion solution. The significant improvement in the anticorrosion resistance of the DLC film was mainly due to the increased sp3 element and formation of the passive film. As a result, the DLC coating deposited on the SUS316L steel at CH4/H2 = 1 : 1 has better anticorrosion properties. However, the DLC film-coated SUS316L steel still cannot meet the corrosive resistance of the bipolar plate.